1990
DOI: 10.4039/ent122817-9
|View full text |Cite
|
Sign up to set email alerts
|

HOST DISCRIMINATION BY A CRUCIFER-FEEDING FLEA BEETLE, PHYLLOTRETA STRIOLATA (F.) (COLEOPTERA: CHRYSOMELIDAE)

Abstract: Can. Ent. 122: 817-824 (1990) The flea beetle, Phyllotreta striolata (F.), was attracted to the cruciferous plants Brassica oleracea L. and Raphanus sativus L., but not to B. campestris L. and B. napus L. which are important natural host plants, nor to Pisum sativum (L.), a legume. The presence or absence of attraction was demonstrated by exposing small groups of caged plants to natural populations and trapping beetles near the plants. In choice and nochoice laboratory feeding experiments, P. striolata fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
1
25
0
Order By: Relevance
“…Bodnaryk (1992) showed that S. arvensis from Manitoba could serve as a host for the flea beetle, Phyllotreta cruciferae (Chrysomelidae). In caged feeding trials in Manitoba, Lamb and Palaniswamy (1990) found that the striped flea beetle P. striolata (F.) fed on eight crucifers in the genera Brassica, Raphanus and Sinapis and not on the legume Pisum; it also fed less on S. arvensis and S. alba than on plants in the other genera.…”
Section: Response To Parasitesmentioning
confidence: 99%
“…Bodnaryk (1992) showed that S. arvensis from Manitoba could serve as a host for the flea beetle, Phyllotreta cruciferae (Chrysomelidae). In caged feeding trials in Manitoba, Lamb and Palaniswamy (1990) found that the striped flea beetle P. striolata (F.) fed on eight crucifers in the genera Brassica, Raphanus and Sinapis and not on the legume Pisum; it also fed less on S. arvensis and S. alba than on plants in the other genera.…”
Section: Response To Parasitesmentioning
confidence: 99%
“…Several species of oligophagous leaf beetles (Coleoptera: Chrysomelidae) also have been reported to show preference for some host plants over others. For example, the striped ßea beetle, Phyllotreta striolata (F.) was shown to discriminate among its host plants in the family Brassicaceae, preferring some hosts such as Brassica oleracea, B. napus, and B. campestris over B. juncea (L.) Czern and B. nigra (L.) Koch (Lamb andPalaniswamy 1990, Anderson et al 1992). The Colorado potato beetle, Leptinotarsa decemlineata (Say) also demonstrated host preference to its host plants, preferring potato (Solanum tuberosum L.) over tomato (Lycopersicon esculentum L.) and eggplant (Solanum melongena L.).…”
Section: Discussionmentioning
confidence: 96%
“…Feeding tests have been used before to quantify resistance in Brassica crops to several insect pests ( Dunn & Kempton, 1976;Eigenbrode et al , 1990;Lamb & Palaniswamy, 1990 ). Picoaga et al (2003) evaluated the performance of several kale varieties from northwestern Spain to lepidopterous pests and found variation in resistance.…”
Section: Introductionmentioning
confidence: 99%